AI-thinking in secondary mathematics education: A design-based research on Bayesian-based probabilistic reasoning - Pramartha, I Nyoman Bagus; Hendriyanto, Agus; Muhaimin, Lukman Hakim (Universitas Islam Negeri Raden Intan Lampung, 2026)
The integration of Artificial Intelligence (AI) in mathematics education often treats it as a